Substrate‐Selective Catalysis. Issue 42 (3rd October 2014) - Lindbäck, Emil; Dawaigher, Sami; Wärnmark, Kenneth
Abstract Substrate selectivity is an important output function for the validation of different enzyme models, catalytic cavity compounds, and reaction mechanisms as demonstrated in this review. In contrast to stereo‐, regio‐, and chemoselective catalysis, the field of substrate‐selective catalysis is under‐researched and has to date generated only a few, but important, industrial applications. This review points out the broad spectrum of different reaction types that have been investigated in substrate‐selective catalysis. The present review is the first one covering substrate‐selective catalysis and deals with reactions in which the substrates involved have the same reacting functionality and the catalysts is used in catalytic or in stoichiometric amounts. The review covers real substrate‐selective catalysis, thus only including cases in which substrate‐selective catalysis has been observed in competition between substrates.